Platinum Group Minerals in Eastern Brazil GEOLOGY AND OCCURRENCES IN CHROMITITE AND PLACERS - Angeli, Nelson (Johnson Matthey Publ Ltd Co, 2005)
Brazil does not have working platinum mines, nor even large reserves of the platinum metals, but there is platinum in Brazil. In this paper, four massifs (mafic/ultramafic complexes) in eastern Brazil, in the states of Minas Gerais and Ceara, where platinum is found will be described. Three of these massifs contain concentrations of platinum group minerals or platinum group elements, and gold, associated with the chromitite rock found there. In the fourth massif, in Minas Gerais State, the platinum group elements are found in alluvial deposits at the Bom Sucesso occurrence. This placer is currently being studied.